Copy of a telegram from the Homburgers, April 4, 1941 - Homburger, Marianne; Homburger, Viktor (1941)
Viktor (1888-1968) and Marianne Homburger (1903-1986) discuss their options for obtaining passage to the United States from France.
Keywords: Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Jewish Holocaust (1939-1945); Emigration and immigration; Political refugees